What is the most effective treatment for a patient with symptoms of chronic mucocutaneous candidiasis (CMC)?. Issue 3 (March 2016) - Trietley, Gregory S.; Shelesky, Gretchen; Haugh, Amy; Wilson, Stephen A.
Abstract : Evidence‐Based Answer : For patients with CMC, 6‐month therapy with a systemic azole may be effective (SOR: B, single RCT). Daily oral fluconazole has been recommended as first‐line treatment (SOR: C, expert opinion). Should resistance develop, treatment should be individualized based on Candida albicans culture susceptibility and clinical response; options include posaconazole, echinocandins, and amphotericin B, with the need for maintenance antifungal therapy likely (SOR: C, case reports and expert opinion).